Family portrait
Two men, two women, and a young boy seated in a living room. Left to right: Christine "Tiny" Albanese McArthur, Dr. Charlie McArthur, Marvie McArthur, Marian Talesfore Keagy, and Don Keagy. Dr. Charlie McArthur and Don Keagy are in military uniform.